Penerapan Metode Peramalan Penjualan Sebagai Dasar Penetapan Perencanaan Jumlah Produksi Pada Home Industri Roti Setia Bakery Di Adirejo, Lampung Timur - Suryadi, Suryadi; Septiana, Nani; Hasanah, Avianti Nur (Jurnal Manajemen DIVERSIFIKASI, 2023)
This study aims to determine the right forecasting method used in the home industry of Roti Setia Bakery and to determine the number of products that must be produced by the home industry of Roti Setia Bakery from June 2022 to May 2023. The type of research used is quantitative research. This study uses the semi-average method and the least square method. The results of this study are based on the MAPE level (mean absolute percentage error) of the two methods, so the sales forecasting method that is more appropriate is used in the Home Industry of Roti Setia Bakery using the semi-average method because it has smaller deviations. by 5.62% compared to using the least square method (least square method), namely MAPE of 13.33%. Planning for the amount of bread production at the Setia Bakery Home Industry Bread in the June 2022 period is 1,225.30 pcs, the July 2022 period is 1,228.13 pcs, the August 2022 period is 1,230.96 pcs, the September 2022 period is 1,233.79 pcs, the October 2022 period 1236.62 pcs, November 2022 period 1,239.45 pcs, December 2022 period 1,242.28 pcs, January 2023 period 1,245.11 pcs, February 2023 period 1,247.94 pcs, March 2023 period 1,250.77 pcs, April 2023 period is 1,253.60 pcs, May 2023 period is 1,256.43 pcs.